Can the 50-g oral glucose tolerance test predict macrosomia and large for gestational age in pregnant women without gestational diabetes? (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate the relationship between the results of the 50-g oral glucose tolerance test (OGTT) and macrosomia and large for gestational age (LGA) in non-gestational diabetes mellitus (GDM) pregnant women.Materials and Methods: Our retrospective study comprised 980 pregnant women18–40 years old, within 24–28 weeks of gestation, and having a singleton pregnancy. GDM was screened using the 50-g OGTT. Patients were divided into three groups according to the OGTT results as follows: (1) 1-h plasma glucose levels >140 mg/dL and normal 100-g OGTT results (false-positive group), (2) 1-h plasma glucose levels between 130 and 139mg/dL, and (3) 1-h plasma glucose levels
Keywords: False-positive screening; gestational diabetes mellitus; large for gestational age; macrosomia; 50-g OGTT